COMPARATIVE STUDIES OF COVID-19 IMPACT ON STUDENTS’ VIEWS ON DIGITAL HIGHER EDUCATION - Ahrens, Andreas; Zascerinska, Jelena; Bhati, Parulkumari P; Zascerinskis, Mihails; Aleksejeva, Anastasija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Higher education sector has been significantly adapting to the new situation created by the COVID-19 pandemic. Despite students are often referred to, students are rarely at the centre of the concerns being raised. The research aim is to compare students’ views on digital higher education in light of COVID-19 underpinning the identification of issues in digital higher education in light of COVID-19. The research implies theoretical and empirical methods. The exploratory empirical study was carried out. Semi-structured interviews serves as the data collection method. Content analysis was applied to the obtained data for data processing. The theoretical analysis allows finding that digital environment in higher education is not limited by only a technical aspect of its organisation. Digital environment also implies students’ health, financial and economic situation, etc. The empirical findings contribute to the conclusion that digital higher education in light of COVID-19 is negatively evaluated by students. The most common issues faced by students are identified. The research question is newly formulated. Directions of further research are proposed. The novelty of the paper is presented by the identified issues in digital higher education in light of COVID-19.